Bio‐inspired spontaneous splitting of underwater bubbles along a superhydrophobic open pathway without perturbation. Issue 1 (29th July 2022) - Li, Xin; Zhang, Jianqiang; Wang, Xuejiao; Lv, Dong; Cao, Chunyan; Ai, Liqing; Yao, Xi
Abstract: Bubbles are pervasive in aqueous media, and on account of numerous advantages of tiny bubbles, efficient bubble splitting is favorable in a wide range of applications. However, underwater bubble splitting faces a lot of challenges because bubbles tend to coalesce during the rising due to the action of buoyancy and surface energy, and the consumption of considerable external energy is needed. Inspired by the bubble bursting phenomenon on the feathers of high‐speed swimming penguins, we proposed a new bubble splitting strategy based on the energy conversion of bubble transportation on superhydrophobic open pathways. A porous superhydrophobic coating was first developed via a bubble‐template assisted fabrication method, which provides hierarchical micro/nanostructures and robust air plastron. Gas bubbles can transport along the superhydrophobic open pathways without perturbation, and split into smaller ones by taking advantage of the potential energy contributed by buoyancy. By controlling the superhydrophobic pathway, the size of the split bubbles can be controlled precisely. We also demonstrated that a bubble splitting device could be applied in underwater reactions where an enhanced gas−liquid mass transfer is desired. This bubble splitting strategy may offer new prospects for underwater bubble manipulation and unfold a potential in many bubble‐involved fields. Abstract : Inspired by air plastrons on some creature surfaces and the bubble trail phenomenon observed on high‐speed swimming penguins, we developed a spontaneous bubble splitting strategy, which efficiently converts bubble potential energy into surface energy without any external energy consumption. Gas bubbles can be transported along an open pathway introduced by a porous superhydrophobic coating without perturbation, and split into smaller ones of a controllable size. The strategy offers new insights into bubble transport, and it is promising to be applied in many fields.